Innate Immune Pathways Associated with Lung Radioprotection by Soy Isoflavones - Abernathy, Lisa M.; Fountain, Matthew D.; Joiner, Michael C.; Hillman, Gilda G. (Frontiers in Oncology, 2017)
Introduction: Radiation therapy for lung cancer causes pneumonitis and fibrosis. Soy isoflavones protect against radiation-induced lung injury, but the mediators of radioprotection remain unclear. We investigated the effect of radiation on myeloid-derived suppressor cell (MDSCs) in the lung and their modulation by soy isoflavones for a potential role in protection from radiation-induced lung injury. Methods: BALB/c mice (5-6 weeks old) received a single 10 Gy dose of thoracic irradiation and soy isoflavones were orally administrated daily prior to and after radiation at 1 mg/day. Arginase-1 (Arg-1) and NF-kB p65 were detected in lung tissue by western blot and immunohistochemistry. Lung MDSC subsets and their Arg-1 expression were analyzed by flow cytometry. Cytokine levels in lungs were measured by ELISA. Results: At 1 week after radiation, CD11b+ cells expressing Arg-1 were decreased by radiation in lung tissue yet maintained in lungs treated with radiation and soy isoflavones. Arg-1 was predominantly expressed by CD11b+Ly6ClowLy6G+ granulocytic MDSCs (gr-MDSCs). Arg-1 expression in gr-MDSCs was reduced by radiation and preserved by supplementation with soy isoflavones. A persistent increase in Arg-1+ cells was observed in lung tissue treated with combined radiation and soy isoflavones at early and late time points, compared to radiation alone. The increase in Arg-1 expression mediated by soy isoflavones could be associated with the inhibition of radiation-induced activation of NF-κB and the control of pro-inflammatory cytokine production demonstrated in this study. Conclusion: A radioprotective mechanism of soy isoflavones may involve the promotion of Arg-1 expressing gr-MDSCs that could play a role in downregulation of inflammation and lung radioprotection.